2013
DOI: 10.21897/rmvz.198
|View full text |Cite
|
Sign up to set email alerts
|

Estructura genética poblacional del gen lactoferrina bovino en vacas Holstein del departamento de Antioquia

Abstract: RESUMENObjetivo. Estimar algunos parámetros de estructura poblacional en una población Holstein del departamento de Antioquia. Materiales y métodos. El estudio se realizó con 427 vacas de la raza Holstein pertenecientes a 5 municipios del departamento de Antioquia. La genotipificación se llevó a cabo usando la técnica de PCR-PFLPs. La Heterocigocidad observada (Ho) y Heterocigocidad esperada (He), la prueba de Hardy-Weinberg (HW) y la estructura y diferenciación genética entre las poblaciones se calculó median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
3
1
4
Order By: Relevance
“…This could explain the genetic differentiation found among subpopulations in the department of Antioquia; although there is genetic flux between them, it has not been sufficient to homogenize the allelic frequencies, although it could be thought that the populations are in a process of homogenization. In other studies (4,19), the number of migrants that has been reported is much greater than what was found in this investigation. Based on a SNP, the growth hormone gene (bGH) was reported for the Holstein population in Antioquia at Nm=36 (4), while based on the SNP of the lactoferrine gene (LTF), Nm=25 has been reported for the same population (19).…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…This could explain the genetic differentiation found among subpopulations in the department of Antioquia; although there is genetic flux between them, it has not been sufficient to homogenize the allelic frequencies, although it could be thought that the populations are in a process of homogenization. In other studies (4,19), the number of migrants that has been reported is much greater than what was found in this investigation. Based on a SNP, the growth hormone gene (bGH) was reported for the Holstein population in Antioquia at Nm=36 (4), while based on the SNP of the lactoferrine gene (LTF), Nm=25 has been reported for the same population (19).…”
Section: Discussioncontrasting
confidence: 79%
“…Esto podría explicar la diferenciación genética encontrada entre las subpoblaciones del departamento de Antioquia; aunque existe flujo genético entre ellas este no ha sido suficiente para homogenizar las frecuencias alélicas, sin embargo se puede pensar que las poblaciones se encuentran en un proceso homogenización. En otros estudios (4,19) se ha reportado un número de migrantes mucho mayor al encontrado en esta investigación. Con base en un SNP del gen de hormona de crecimiento (bGH) se reportó para la población Holstein de Antioquia un Nm=36 (4), mientras que con base en un SNP del gen de lactoferrina (LTF) se ha reportado un Nm=25 para la misma población (19).…”
Section: Discussionunclassified
See 3 more Smart Citations